Psychosis and psychedelics: Historical entanglements and contemporary contrasts. - Friesen, Phoebe (Transcultural Psychiatry, 2022)
Experiences of psychedelics and psychosis were deeply entangled in scientific practices in the mid-20th century, from uses of psychedelic drugs that could model psychosis, to detailed phenomenological comparisons of endogenous and drug-induced madness. After the moral panic of the 1960s shut down psychedelic research, however, these two phenomena became disentangled. In the decades following, the science of psychosis transformed, shedding the language of psychoanalysis, and adopting the new scientific veneer of psychiatry. Today, as psychedelic science re-emerges, the research programs surrounding psychosis and psychedelics now stand in stark contrast. Here, I look closely at how these research programs respond to questions related to what is worth measuring, what is worth investigating, and how we ought to respond to these experiences. This comparison reveals radically different assumptions and values that guide each research paradigm and shape clinical practice. While psychedelic research often includes scales that seek to capture experiences of mysticism, meaningfulness, and ego dissolution, research related to psychosis focuses on the measurement of pathological symptoms and functioning. Research into psychosis primarily seeks universal and reductionist causal explanations and interventions, while psychedelic research embraces the importance of set and setting in shaping unique experiences. Responses to psychedelic crisis involve warmth, compassion, and support, while responses to psychotic experiences often involve restraint, seclusion, and weapons. I argue that these differences contain important lessons for psychiatry. However, as psychedelic research struggles to meet regulatory requirements and fit within the paradigm of evidence-based medicine, these differences may quickly dissolve.